What have we learned? Assessing labor market institutions and indicators - Eichhorst, Werner; Feil, Michael; Braun, Christoph (Bonn, 2008)
"Over the last decade, both the availability of quantitative indicators on labor market institutions and of studies trying to explain differences in national labor market performance through institutional variables have burgeoned significantly. It is now time to review these indicators and the empirical findings. Therefore, this paper has a threefold objective: first, we provide an overview of the aggregate indicators of core labor market institutions such as employment protection, the generosity of the benefit system, active labor market policies, taxation and collective bargaining. We assess the reliability of selected indicators. Second, we review the most relevant macro-econometric studies that made use of these indicators in order to explain diverging patterns of national employment performance. Third, and finally, this paper draws some preliminary conclusions regarding the further development of aggregate indicators and possible directions for future empirical research."